2012
DOI: 10.1177/0255761411434499
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and perceptual measures of SATB choir performances on two types of portable choral riser units in three singer-spacing conditions

Abstract: Under controlled conditions, we assessed acoustically (long-term average spectra) and perceptually (singer survey, listener survey) six performances of an soprano, alto, tenor, and bass (SATB) choir (N = 27) as it sang the same musical excerpt on two portable riser units (standard riser step height, taller riser step height) with varied dimensions of largely horizontal space (close spacing, lateral spacing, circumambient spacing) between singers. Given previous research that suggested horizontally spread spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
1
20
0
4
Order By: Relevance
“…Singers were laterally spaced using dowel rods measuring 0.61 m (24 in.) so that intersinger distance remained consistent (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013Daugherty et al, , 2019. We projected a conductor video, of the choir's usual conductor demonstrating a pattern and tempo similar to that of the previous performance, on the back wall of the recital hall as to not impede microphone placement.…”
Section: Choir Recording Session Proceduresmentioning
confidence: 99%
“…Singers were laterally spaced using dowel rods measuring 0.61 m (24 in.) so that intersinger distance remained consistent (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013Daugherty et al, , 2019. We projected a conductor video, of the choir's usual conductor demonstrating a pattern and tempo similar to that of the previous performance, on the back wall of the recital hall as to not impede microphone placement.…”
Section: Choir Recording Session Proceduresmentioning
confidence: 99%
“…Daugherty concluded that singer spacing may have a greater effect on choral sound than formation (e.g., mixed vs. sectional). In experiments with both auditioned and nonauditioned high school and university ensembles, he consistently found that both singers and listeners preferred spread spacing of at least 2 ft between singers over close spacing of one inch (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013;Daugherty et al, 2019). Adams (2019a) concluded that both large and chamber university ensembles also preferred spread spacing (2 ft) over moderate (1 ft) or close Update 39 2(1 in.)…”
Section: Intrasection Singer Configurationmentioning
confidence: 99%
“…For individual singers, the change in overall spectral shape in the frequency region above 2.4 kHz, the timbral region, will relate to the extent to which that individual's singing voice will stand out within the overall choral sound and the degree to which that singer can blend in with other voices. The physical position of individual members of the choir relative to other members can have a significant effect on the overall voice line and therefore the total acoustic output from the choir [35,36]. Attention paid to this aspect through voice matching and physical placement of individual singers provides a practical means of taking advantage of this effect in practice.…”
Section: Development Of Sound Modifier Control In the Female Choir Voicementioning
confidence: 99%